Mapping Sovereign Wealth Fund Strategies for Energy Transition and Sustainable Development: A Two-Decade Bibliometric Analysis - Mota, Teodoro Marcos; Adityawarman, Adityawarman; Ariadji, Tutuka; Dewi, Retno Gumilang; Naikosou, Marcelino Freitas; Guterres, Mario Viana; Samawi, Nabil Visi; Saldanha, Estanislau de Sousa (International Journal of Energy Economics and Policy, 2026)
This paper provides a systematic overview of the development of scholarly research on SWF strategies by examining key thematic patterns, prominent contributors, institutional involvement, and long-term publication dynamics through a bibliometric lens. The study is based on a dataset of 171 peer-reviewed articles retrieved from the Scopus database, covering the period from 2008 to 2025. Multiple bibliometric techniques including citation analysis, co-citation mapping, bibliographic coupling, co-authorship analysis, and keyword co-occurrence were applied using VOSviewer and the Bibliometrix package to ensure analytical rigor and transparency. The results identify five dominant research clusters within the SWF literature: macroeconomic and political dimensions, ESG and sustainability-oriented strategies, institutional investment behavior, financial performance outcomes, and country-specific or contextual perspectives. Although academic interest in SWFs has grown over time, the literature remains fragmented, with limited international collaboration and insufficient coverage of developing and resource-dependent economies. This study is subject to certain limitations, as it relies solely on publications indexed in the Scopus database, which may result in the underrepresentation of recent high-impact studies due to citation delays or database constraints. Despite these limitations, the findings offer meaningful insights for policymakers, academics, and fund managers by outlining prevailing research trends, identifying underexplored areas, and highlighting opportunities for deeper interdisciplinary and cross-national collaboration. Overall, this study delivers a comprehensive bibliometric synthesis of SWF strategy research and proposes future research directions to support more sustainable and strategically aligned sovereign wealth management practices.